Problem Solving in Mathematics Education - Liljedahl, Peter; Santos-Trigo, Manuel; Malaspina, Uldarico; Bruder, Regina (ICME-13 Topical Surveys,, 2016)
This survey book reviews four interrelated areas: (i) the relevance of heuristics in problem-solving approaches - why they are important and what research tells us about their use; (ii) the need to characterize and foster creative problem-solving approaches - what type of heuristics helps learners devise and practice creative solutions; (iii) the importance that learners formulate and pursue their own problems; and iv) the role played by the use of both multiple-purpose and ad hoc mathematical action types of technologies in problem-solving contexts - what ways of reasoning learners construct when they rely on the use of digital technologies, and how technology and technology approaches can be reconciled. .